Usefulness of absorption techniques in doubtful cases of incompatibility Rh maternal fetal: a case report - Donno, Eleonora; Di Monte, Jessica; Di Mascio, Manuela; Orsini, Tiziana; Di Valerio, Annalisa; Pinti, Luisa; Massaro, Paola; Scardapane, Seila; Fusilli, Francesca; Salvatore, Franco; Procida, Amalia; Esposito, Antonio (Journal of Biomedical Practitioners, 2023)
INTRODUCTION This case report traces the diagnostic and therapeutic process of the Immuno-Transfusion Service in a case of fetal anaemia characterized by various inconsistencies between clinical and laboratory data. The paper describes an alternative technique implemented with the aim of resolving incompatibilities between positive IAT and negative DAT. In addition, the algorithm necessary to reach a diagnosis in a transfusion medicine laboratory is traced, namely, the performance of first- and second-level immuno-haematological tests, the evaluation of fetal clinical signs, and the preparation of blood components necessary for intrauterine transfusion. CASE PRESENTATION The case involves a pregnant woman who comes to the Immuno-Transfusion Service following a positive Indirect Antiglobulin Test and fetal anaemia. The main questions relate not only the presence of immunization in the woman, which should have been avoided by immunoprophylaxis (being group 0 Rh negative), but also the stability of the antibody titer (or level) throughout the pregnancy, fetal recovery after TIU, and the presence of a negative Direct Antiglobulin Test. CONCLUSIONS Questions that were completely resolved at caesarean section with the discovery of a giant chorioangioma that, by sequestering fetal red blood cells, caused anaemia and the confirmation of a rare blood phenotype of the father that caused the woman's immunization.